STUDY OF ADAPTATION SIMULATION ON TERMAL COMFORT- ABLENESS LEVEL CAUSED BY GLOBAL CLIMATE CHANGE ON PADANG - Sugeng Nugroho (Pusbindiklat - LIPI, 2011)
Climate change will affect the thermal comfortableness level in the urban area therefore adaptation is needed to reduce its impact. Thermal comfortableness level was determined base on climate scenario data emission A2 and B2 on the period of 1961-2100. Adaptation simulation is conducted by modifying mean radiant temperature, increasing wind speed and cloth coeffi cient value on the thermal comfortableness level calculation. Result showed that generally, thermal comfortableness level in Padang on the period of 1961-2100 was in the uncomfort level category. Adaptation simulation which had the most infl uence on the thermal comfortableness level was by modify-ing mean radiant temperature and increasing wind speed on the original data.